Pattern of susceptibility to measles in Italy - Stefania Salmaso; Giovanni Gabutti; Maria Cristina Rota; Cristina Giordano; Cleonice Penna; Donatella Mandolini; Pietro Crovari (The World Health Organization, 2000)
On the basis of seroprevalence and incidence data we describe the distribution of individuals susceptible and immune to measles in Italy in 1996-97. In regions where vaccination coverage was at least 70%, approximately 10% of 3-year-old children were susceptible to measles, whereas 40% were in this category in regions with lower vaccination coverage. Seroprevalence among children older than 4 years was similar for the two groups of regions; in the age group 20-39 years it was approximately 95%. During 1990-96 in the regions with lower vaccination coverage the incidence was highest among children aged 4-6 years, and the median age of cases was 7 years; in the regions with higher vaccination coverage, however, the incidence remained at around 5% for the age group 4-16 years, and the overall median age was 10 years. These data confirm the partial reduction in measles incidence in Italy, although transmission has still not been interrupted. The size and geographical distribution of the current pool of susceptible individuals can be expected to present an obstacle to measles elimination if appropriate vaccination strategies, such as catch-up campaigns, are not adopted.